A Review on the Efficacy and Safety of Nab-Paclitaxel with Gemcitabine in Combination with Other Therapeutic Agents as New Treatment Strategies in Pancreatic Cancer - Christian Chapa-González; Karina López; Kimberly Michelle Lomelí; Jorge Alberto Roacho-Pérez; Jazmín Cristina Stevens (Life, 2022)
Pancreatic cancer has one of the highest mortality rates among cancers, and a combination of nab-paclitaxel with gemcitabine remains the cornerstone of first-line therapy. However, major advances are required to achieve improvements in patient outcomes. For this reason, several research groups have proposed supplementing treatment with other therapeutic agents. Ongoing studies are being conducted to find the optimal treatment in a first-line setting. In this work, we used a search strategy to compare studies on the efficacy and safety of nab-paclitaxel with gemcitabine in combination with other therapeutic agents based on the criteria of the Preferred Reporting Items for Systematic Reviews. We found seven studies in different clinical phases that met the inclusion criteria. The seven therapeutic agents were ibrutinib, necuparanib, tarextumab, apatorsen, cisplatin, enzalutamide, and momelotinib. Although these therapeutic agents have different mechanisms of action, and molecular biology studies are still needed, the present review was aimed to answer the following question: which formulations of the nab-paclitaxel/gemcitabine regimen in combination with other therapeutic agents are safest for patients with previously untreated metastatic pancreas ductal adenocarcinoma? The triple regimen is emerging as the first-line option for patients with pancreatic cancer, albeit with some limitations. Thus, further studies of this regimen are recommended.